New Insights into the Estimation of Impact Load of Granular Flow against a Rigid Wall - Xiao Siyou; Yang Junwei; Wei Zhongju (Shock and Vibration)
The installation of a rigid wall is a main approach to mitigate a granular flow. The methods of the impact load against a rigid wall still remains a challenge. In this study, the progresses in the estimation of the impact load of granular flow against a rigid wall are introduced in detail. The influences of the slope angle, the installed angle of rigid wall, the volume of granular flow are not fully considered into the present models. The discrete element method is employed to reveal the effects of these factors on the impact load. The numerical results show that the volume of granular flow is a key factor to determine the evolution of the impact load on a rigid wall. The dynamic impact load of granular flow at the initial stage is decided by the angle between the rigid wall and slope surface. If the installation angle is same, the slope angle mainly determines the static load of granular flow. Based on these findings, we propose simplified model that the relationship between the impact load and the multiple physical parameters, such as slope angle, installation angle, repose angle, flow height and flow velocity, basal friction angle, and the volume of granular flow, is taken into account.